Sholawat Tradition and Conflict Resolution: A Case Study of the Kotarindau Pilgrimage Council in Sigi Regency - Ikram, Moh.; Khadiq (Indonesian Academy of Social and Religious Research (IASRR), 2024)
This research aims to explore the role of religion in dealing with inter-village conflicts through a case study at the Kotarindau Village Pilgrimage Council, Dolo District. Through a qualitative approach, this research will explore various activities carried out by the Pilgrimage Council and the role of religion in overcoming and preventing conflicts that may arise between villages in Dolo District. The research methods used include participatory observation, in-depth interviews with members of the Pilgrimage Council and related stakeholders, and analysis of documents related to activities and conflicts. The Pilgrimage Council creates a safe and loving space through religious activities such as congregational prayers, religious studies, and pilgrimages to the graves of predecessors. This deepens people's spirituality and builds soul strength to maintain daily harmony. This research also suggests further research regarding the Kotarindau Pilgrimage Council, especially in comprehensive documentation and understanding of programs such as the celebration of the Majlis's Milad, the Prophet's birthday, pilgrimages to the graves of respected elders, as well as socio-religious activities such as the Pilgrimage Council's contribution to people with disabilities. In Sigi Regency, this could be the focus of future research at the Pilgrimage Council.